(untitled) (International Journal of Engineering and Computer Science, 2017)
The Unified Modeling Language (UML) is becoming widely used for software and database modeling, and has been accepted by the Object Management Group as a standard language for object-oriented analysis and design. In This paper We compare different UML tool and there Pros & Cons with case study